The correlation Between Auditory Learning Style’gradeand Students’ Speaking Skill - Siti Hozaimah (Graduate Program, University of Islam Malang, 2019)
The main goal in learning is to comprehend, to understand to practice and to implement. It is aimed to get the optimal comprehension and understanding in learning. To get the aim and goal of learning, it depends on how learners have the ways in learning style. How a learner comprehend is the focus of the concept and method of learning style. Learning styles can be determined and defined as characteristic cognitive, affective, and physiological behaviors that serve as relatively stable indicators of how learners perceive, interact with, and respond to the learning environment.Three kinds of learning style are; 1) visual, 2) Auditory, and 3) kinesthetic. This study and research focus on auditory learning style only. The way how students learning by relying on their listening process is determided by Auditory learning style. learnersprefer to listen the discussion, presentation and speech better than to read more.The most impertant of learning style which must be learned is Speaking skill because It hasclose relation with other skills. Those are listening, reading and writing. Therefore, thisstudy wants to show the correalation between auditory learning style toward student’s speaking skill.Based on the description and explanation above,a research problem in this studyis “Is there significant correlation between auditory learning style and students’ speaking skill”.This present research study was conducted to investigate whether there is a significant correlation between the students’ auditory learning style and their speaking skill or not. This study uses quantitative research and the reseacher uses the correlation design. There are two variables investigated in this study, those are: the students’ auditory learning style as independent variable and speaking skill as dependent variable.The population in this research is all the students of the eleventh grade of Madrasah Aliyah Al-mujtama’ Madura which consist of 38 students. Because the population is less than 100 objects, so it is called by population research design. The instrument to be implemented to collect the data was questionnaire to get data variable X (Auditory learning style) and test for variable X (speaking skill). This instrument was applied to know the students’ score. Then, the data was analyzed by using the correlation analysis of spearman brown formula. The result shows that the value of ρ (or rs) in this research is 0.965 with the significant 0.000. It means that there is significant correlation between students’ Auditory learning style and speaking skill. So, the alternative hypothesis (Ha) in this research which stated that there is a significant correlation between the students’ Auditory learning style and their speaking skill is accepted. Keyword : auditory learning style, speaking